ショウワキチ チカク ノ ロガン チタイ デ エラレタ ダニ - 大山, 佳邦; オオヤマ, ヨシクニ; 松田, 達郎; マツダ, タツロウ; Ohyama, Yoshikuni; Matsuda, Tatsuro (国立極地研究所, 1977)
P(論文) 第17次南極地域観測隊の生物調査として,昭和基地のあるオングル島をはじめ,リュツォ・ホルム湾の沿岸にある露岩地帯の砂の中から自由生活性のダニ類を採集した.これらのうちからNanorchestes antarcticus, Tydeus erebus, Protereunetes minutusの3種のダニが同定された.オングル島を含むリュツォ・ホルム湾沿岸の露岩地帯からこれらのダニが報告されるのは最初である. As one of the biological programmes of Japanese Antarctic Research Expedition, the collection of free-living mites was made at sandy habitats of the following ice-free areas in Lutzow-Holm Bay in January and February, 1976: East Ongul Island, West Ongul Island, Langhovde and Skarvsnes. The three species of prostigmatic mites were identified from the collection as follows: Nanorchestes antarcticus, Tydeus erebus and Protereunetes minutus. This is the first record on these mites from the ice-free areas mentioned above. departmental bulletin paper